2002
DOI: 10.1194/jlr.m200165-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

A novel soluble analog of the HIV-1 fusion cofactor, globotriaosylceramide (Gb3), eliminates the cholesterol requirement for high affinity gp120/Gb3 interaction

Abstract: We have analyzed the interaction of adamantyl Gb 3 (adaGb 3 ), a semi-synthetic soluble analog of Gb 3 , with HIV-1 surface envelope glycoprotein gp120. In this analog, which was orginally designed to inhibit verotoxin binding to its glycolipid receptor, Gb 3 , the fatty acid chain is replaced with a rigid globular hydrocarbon frame (adamantane). Despite its solubility, adaGb 3 forms monolayers at an air-water interface. Compression isotherms of such monolayers demonstrated that the adamantane substitution res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 50 publications
(94 reference statements)
4
60
1
Order By: Relevance
“…In contrast, a distinct fluorescent band was formed for Gb 3 +cholesterol. However adaGb 3 formed the strongest labeled 'raft' band (Mahfoud et al, 2002b). While the characteristics of the structures formed by adaGb 3 in this band remain to be fully characterized, this supports the "raft-like" character of adaGb 3 .…”
Section: Defining a New Assay For Lipid Raft Formationsupporting
confidence: 47%
See 3 more Smart Citations
“…In contrast, a distinct fluorescent band was formed for Gb 3 +cholesterol. However adaGb 3 formed the strongest labeled 'raft' band (Mahfoud et al, 2002b). While the characteristics of the structures formed by adaGb 3 in this band remain to be fully characterized, this supports the "raft-like" character of adaGb 3 .…”
Section: Defining a New Assay For Lipid Raft Formationsupporting
confidence: 47%
“…In collaboration with Fantini's group , we showed that gp120 can insert into a Gb 3 monolayer at the water/air interphase in a Langmuir trough (Mahfoud et al, 2002b). However, there was a 2 hour lag-phase prior to binding/insertion which then proceeded at a sigmoidal rate.…”
Section: Generation Of Gsl Mimicsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16] The aqueous solubility of the resulting compounds has been reported to be significantly increased, which could be attributed to the formation of low-order aggregates. [16,17] In addition, the rigid globular hydrocarbon framework of adamantane groups may facilitate the crystallisation processes. Furthermore, they may also mimic the actual behaviour and conformation of the long acyl chains of naturally occurring phosphoinositides in vivo when exposed to the buffer-like cytosolic environments.…”
Section: Introductionmentioning
confidence: 99%